Archaeological Encounters: The Role of the Speculative in Decolonial Archaeology - Rizvi, Uzma (Journal of Contemporary Archaeology, 2019)
This article reorients archaeology’s approach to things by acknowledging the moment of the encounter with the past as one of speculation. Years of scientific claim, research design and methodology place the agentive nature of research in the hands of the archaeologist: we go to the site to find the past. However, if we acquiesce to the possibility that antiquity approaches the archaeologist (rather than vice versa), then that forces us to contend with the contemporary nature of the encounter. This article considers the efficacy, urgency, and poetics of decolonization.